Exercise as a mediator of wellbeing - Jiang, Shiya; Zhang, Hao (Frontiers in Psychology, 2025)
IntroductionRecent studies have highlighted physical exercise’s potential impact on college students’ psychological wellbeing. This study aims to explore this relationship further by examining physical fitness’s mediating role.MethodsA comprehensive questionnaire was distributed to 386 college students, and the collected data were analyzed using advanced statistical techniques to ensure high reliability (α = 0.982) and validity (KMO = 0.947).ResultsThe results indicated that exercise habits were significantly influenced by the student’s gender and academic major. Furthermore, a notable correlation was observed between physical fitness and psychological wellbeing, with physical fitness also serving as a partial mediator in this relationship.DiscussionThese findings underscore the importance of promoting physical activity within educational institutions to enhance mental and physical health. The mediating role of physical fitness suggests that improvements in physical condition may be essential for realizing the full psychological benefits of exercise. It supports integrating tailored fitness programs into college wellness initiatives to foster overall student wellbeing.